Contribution of Amaranthus cruentus and Solanum macrocarpon Leaves Flour to Nutrient Intake and Effect on Nutritional Status of Rural School Children in Volta Region, Ghana - Godfred Egbi; Mary Glover-Amengor; Margaret M. Tohouenou; Francis Zotor (Journal of Nutrition and Metabolism)
Background. Plant-based foods are staple diets and main micronutrient sources of most rural Ghanaian households. The objective of this study was to determine the effect of Amaranthus cruentus and Solanum macrocarpon leafy vegetable flour on micronutrient intake and nutritional status of rural Ghanaian school children. Method. This study was a randomized controlled trial that consisted of baseline data collection and a three-month nutrition intervention feeding program. Two groups of 53 children, age 4–9 years, involved in the Ghana School Feeding Program took part in the study. An experimental group consumed Amaranthus cruentus and Solanum macrocarpon leaves flour (ACSMLVF) stews and soup. The control group consumed stews and soup without ACSMLVF. Haemoglobin and serum vitamin A concentrations were determined. Dietary and anthropometric data were collected and analysed. Participants were screened for malaria parasitaemia and hookworm. Results. Anaemia was present in 41.5% and 37.3%, respectively, of the intervention and control groups at baseline. It was present in 28.3% and 53.3%, respectively, at the end of the study. This was significantly different (p=0.024). There was a low vitamin A concentration in 66.0% and 64.7% at baseline and 20.8% and 23.4% at the end of the study in the intervention and control groups, respectively. The mean iron, zinc, and provitamin A (beta-carotene) intakes of the intervention group were 14.2 ± 7.1 mg, 5.7 ± 2.1 mg, and 214.5 ± 22.6 μg, respectively, at baseline. Those of the control were 13.7 ± 6.1 mg, 5.4 ± 2.1 mg, and 210.6 ± 20.1 μg, respectively. At the end of the study, the mean intake of iron, zinc, and beta-carotene for the intervention group was 24.1 ± 10.9 mg, 13.8 ± 8.2 mg, and 694.2 ± 33.1 μg, respectively. The intake of these micronutrients for the control at the end of the study was 14.8 ± 6.2 mg, 5.9 ± 2.3 mg, and 418.4 ± 34.7 μg, respectively. Conclusion. Consumption of ACSMLVF stews and soup increased iron, zinc, and beta-carotene intakes. Anaemia prevalence was lower in the intervention group at the end of the study.